Potential of paleoecology and paleolandscape modeling to identify pre-Colonial cultural burning in montane forests: case studies in California - Klimaszewski-Patterson, Anna (Frontiers in Environmental Archaeology, 2023)
Paleoecology and paleolandscape modeling have the potential to differentiate cultural burning from climatic fires, improving interpretations of past fire histories and vegetation resource management practices. People have conducted variations of traditional fire management to increase terrestrial resources for hundreds of millennia, commonly in fire-prone areas where vegetation is adapted to frequent fire events. Over time, these cultural fires influenced regrowth and led to an anthropogenically-modified landscape. For some non-agrarian, semi-nomadic societies, such as the pre-Colonial groups within what is now known as California, identifying anthropogenic landscapes is difficult because of a lack of domesticated plant remains in the environmental record to indicate where human impacts occurred. This paper uses case studies from the central and southern Sierra Nevada range in California to explore the potential of paleoecology, specifically pollen and sedimentary charcoal, and spatially-explicit paleolandscape modeling to identify and distinguish periods of cultural burning in mountainous forests to improve archaeological interpretations of human-fire dynamics. These cases studies are ideal because (1) the region is naturally fire-prone, (2) study sites are typically well-dated and analyzed at a sub-centennial resolution, (3) study sites are associated with archaeological sites, and (4) indigenous groups were proto-agricultural, balanophagy societies known to practice cultural burning. These case study sites show a strong potential to identify periods of cultural burning that help better inform archaeological interpretations. Furthermore, these studies provide better dated timelines of human influence at each site than nearby archaeological studies, indicating that in certain locales, paleoecological studies with high temporal resolutions could be used to inform the timing of archaeological activities and shifts.